Combining Borrmann and weak‐beam diffraction images to study defects in a high‐quality CdTe(Zn) crystal. Issue 2 (28th February 2023) - Journot, T.; Brellier, D.; Ballet, P.; Tran Thi Caliste, T. N.; Gout, E.; Collonge, D.; Baruchel, J.
Abstract : Synchrotron radiation rocking curve imaging on a highly perfect CdTe(Zn) crystal has been used to study the signatures of second‐phase defects and dislocations in this high‐absorption, Borrmann effect case. Using both the Borrmann image and the weak‐beam image, the depth of the defect within the crystal could be determined. This knowledge acquired on a crystal with only a few defects allows a better understanding of the more complex defect structures present in other crystals. Abstract : In this work, synchrotron radiation rocking curve imaging (RCI) is used to visualize and characterize dislocations and second‐phase defects in a highly perfect and absorbing CdTe(Zn) crystal. This technique requires recording a series of Bragg diffracted images along the rocking curve to produce maps of the `local' integrated intensity, full width at half‐maximum and peak position. The diffraction conditions of the reported experiment are such that anomalous transmission (Borrmann effect) is a crucial ingredient for the formation of the image of the defects. The images recorded and maps produced allow the investigation of a series of topics that, to the authors' knowledge, have not been previously studied. The first of these topics is the variation of the position and width of the Borrmann image of a defect when sitting on the peak and on the flanks of the diffraction curve. The second topic is the way Borrmann images show up on the usual RCI maps. The final topic is the combination of Borrmann and weak‐beam images to infer the depth of the defect within the crystal.